2018
DOI: 10.1097/qad.0000000000001718
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of sexually transmitted infections before and after preexposure prophylaxis for HIV

Abstract: Objective:Use of preexposure prophylaxis (PrEP) for HIV raises concerns about sexually transmitted infection (STI) incidence because of decreased condom use among MSM. This study examines whether PrEP is associated with STIs in the 12 months following PrEP prescription relative to the 12 months prior to PrEP and if STI rates are higher among PrEP users relative to individuals receiving postexposure prophylaxis (PEP).Design:Retrospective cohort study including PrEP users with more than 12 months of follow-up be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
118
8
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(142 citation statements)
references
References 23 publications
(26 reference statements)
11
118
8
5
Order By: Relevance
“…These risk factors were also found in several other studies [3,6,7,14]. Our study complements the results of a recent meta-analysis and other current cross-sectional studies that showed an association between PrEP use and STI diagnosis [30], and reported PrEP use as important risk factor for STI diagnosis [27,40,65]. A large longitudinal study from Australia could even show increasing STI incidences after initiation of PrEP [29].…”
Section: Risk Factors For Stisupporting
confidence: 89%
See 1 more Smart Citation
“…These risk factors were also found in several other studies [3,6,7,14]. Our study complements the results of a recent meta-analysis and other current cross-sectional studies that showed an association between PrEP use and STI diagnosis [30], and reported PrEP use as important risk factor for STI diagnosis [27,40,65]. A large longitudinal study from Australia could even show increasing STI incidences after initiation of PrEP [29].…”
Section: Risk Factors For Stisupporting
confidence: 89%
“…Despite the license of PrEP includes the recommendation of regular condom use for PrEP users, it is probable that one of the main reasons for taking PrEP is that persons can effectively reduce their risk for acquiring a HIV infection without using condoms. Since PrEP was introduced it is under debate to what extent a concomitant reduction of condom use and a potential increase of more risky sexual behavior will lead to an increase of other STI [25][26][27][28][29][30]. In contrast, recommended regular and small meshed STI testing is discussed as an argument against an increase of STI due to PrEP, as this could lead to more efficient diagnosis and treatment of newly acquired STI as well as of so far undiagnosed reservoirs in populations with high risk such as sexually highly active MSM [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent syphilis infection in PLWH can be interpreted as an indicator of altered sexual risk behaviour. Recently, the increased use of pre‐exposure prophylaxis for HIV has raised concerns about greater risk behaviour among MSM and the possibility that this causes a higher incidence in STIs or HPV‐mediated malignancies . The positive correlation between syphilis, HPV infection and AIN highlights the importance of regular STD screening in PLWH and the benefit of promoting safe sex education.…”
Section: Discussionmentioning
confidence: 99%
“…Outra abordagem avaliou a relação entre o uso da PrEP e o aumento do risco de adquirir outras DSTs, principalmente Clamidiose, Gonorreia e Sífilis (NGUYEN et al, 2018). Apesar de haver correlações numéricas, a Truvada® (asnome comercial da associação de Emtricitabina e Tenofovir) não propicia, quimicamente, maior risco à aquisição de doenças sexualmente transmissíveis, porém, pode influenciar nos índices dessas devido mudanças de hábitos que aumentam o risco de tais infecções.…”
Section: Resultsunclassified